STUDIES OF THE ACTIVITY OF DIPHTHERIA TOXIN : I. POLIOVIRUS REPLICATION IN INTOXICATED HELA CELLS - Duncan, J. L. (The Rockefeller University Press, 1967)
It has been demonstrated that a saturating dose of diphtheria toxin produced a 90% inhibition of polio-virus replication in HeLa cells. This inhibition was reflected in infectious viral RNA synthesis and in mature virus production. Toxin had no direct effect on virus particles or I-RNA, and poliovirus adsorption and eclipse appeared to be carried out normally in intoxicated cells. When toxin was given at various time intervals after infection, the amount of inhibition depended on the time of toxin addition. Toxin given before or immediately after infection gave maximum inhibition, while toxin given several hours after infection had little effect. The data suggest that toxin inhibits viral replication through its effect on protein synthesis. It is likely that a critical step in the viral replication cycle, the production of poliovirus-induced RNA polymerase, is inhibited, and possibly the synthesis of capsid protein. Ammonium salts and the aliphatic amines, glycamine and prolamine, prevented the inhibition of viral replication by toxin. The kinetics of the protective action of ammonium chloride and diphtheria antitoxin are remarkably similar.